MAJOR BRANCHES OF PSYCHOLOGY (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Psychology is such a broad field that conveying its depth and breadth can be difficult. As a result, a number of unique and distinctive branches of psychology have emerged, each one dealing with specific psychological areas within the study of the mind, brain, and behavior.